2006
DOI: 10.1016/j.cub.2006.09.044
|View full text |Cite
|
Sign up to set email alerts
|

Ongoing Collapse of Coral-Reef Shark Populations

Abstract: Marine ecosystems are suffering severe depletion of apex predators worldwide; shark declines are principally due to conservative life-histories and fisheries overexploitation. On coral reefs, sharks are strongly interacting apex predators and play a key role in maintaining healthy reef ecosystems. Despite increasing fishing pressure, reef shark catches are rarely subject to specific limits, with management approaches typically depending upon no-take marine reserves to maintain populations. Here, we reveal that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
315
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 296 publications
(333 citation statements)
references
References 22 publications
(31 reference statements)
13
315
2
Order By: Relevance
“…There is a lack of validated age and growth information, limiting the ability of fisheries managers to make informed decisions (Beerkircher and Shivji 2003;Watson et al 2009). In addition, there is insufficient knowledge of their movement patterns that may confound management efforts, exemplified in the ongoing collapse of reef shark populations on the Great Barrier Reef, Australia (Robbins et al 2006), where grey reef sharks, Carcharhinus amblyrhynchos, have been reported to display limited reef fidelity (Heupel et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…There is a lack of validated age and growth information, limiting the ability of fisheries managers to make informed decisions (Beerkircher and Shivji 2003;Watson et al 2009). In addition, there is insufficient knowledge of their movement patterns that may confound management efforts, exemplified in the ongoing collapse of reef shark populations on the Great Barrier Reef, Australia (Robbins et al 2006), where grey reef sharks, Carcharhinus amblyrhynchos, have been reported to display limited reef fidelity (Heupel et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Many species of sharks and rays are under increasing pressure around the world including the GBR (Robbins et al 2006;Heupel et al 2009). Sharks and rays perform important ecological roles in marine ecosystems (Stevens et al 2000;Kitchell et al 2002;Heithaus et al 2008) and growing concerns have prompted GBR managers to list shark conservation and management as a priority issue (GBRMPA 2009a).…”
Section: Introductionmentioning
confidence: 99%
“…The viability of certain shark populations is of global concern (Robbins et al 2006;Dulvy et al 2008;Ferretti et al 2008). Many shark species that are targeted commercially, caught and harvested as bycatch, or captured incidentally and released by recreational or commercial fishers are at risk of over-exploitation and possible extinction (Baum et al 2005;Campana et al 2006;Myers et al 2007).…”
Section: Introductionmentioning
confidence: 99%